Social determinants of health: Building knowledge through social mapping (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2015)
INTRODUCTION: To document methodological routes for the collective construction of knowledge through the use of social cartography and the Social Determinants of Health model applied to Speech Therapy. METHODS: Qualitative research with a grounded theory approach. The data collection techniques correspond to social cartography and the Social Determinants of Health (SDH) model. RESULTS: Based on the social cartography, the statements of the social actors about their relationship with the territory were organized from two places: (a) Temporal access, corresponding to the images of present, past and future; and (b) Categories of analysis, including perceptions associated with (1) conflicts; (2) support networks; (3) infrastructure; and (4) socio-economics. ANALYSIS AND DISCUSSION: The conflict category was the most developed by the social actors, particularly due to the effect of the perceived security in public spaces. The second most relevant category corresponded to support networks, within which a crisis regarding the local representativeness of governance was enunciated. CONCLUSION: Social mapping is a methodological route for accessing the territory and the DSS model. The use of social mapping in speech therapy requires procedural adaptations.
Keywords: Social Health Determinants; Territory; Cartography; Speech Language Pathology